Long term efficacy and safety profile of dexamethasone intravitreal implant in retinal vein occlusions: a systematic review - Carnevali, Adriano; Bacherini, Daniela; Metrangolo, Cristian; Chiosi, Flavia; Viggiano, Pasquale; Astarita, Carlo; Gallinaro, Valentina; Bonfiglio, Vincenza M. E. (Frontiers in Medicine, 2024)
Retinal vein occlusion (RVO) is a vascular condition that poses a threat to sight. It can impact individuals of any age, though its incidence tends to rise with advancing age. Primarily due to its multifactorial nature, treating RVO remains a significant clinical challenge. Various strategies are currently employed for its treatment, encompassing laser photocoagulation (particularly for branch BRVO or as a rescue therapy), vascular endothelial growth factor inhibitors (anti-VEGF), and intravitreal corticosteroids. The current systematic review without meta-analysis aimed to provide an updated summary of the efficacy and safety profile of the sustained release intravitreal dexamethasone implant (DEX-i) for the treatment of macular edema (ME) secondary to either central RVO or branch RVO. Based on current evidence, DEX-i has shown significant enhancements in both best-corrected visual acuity (BCVA) and reduction of central retinal thickness (CRT) in eyes with ME secondary to RVO, encompassing both branch and central types, with rapid and sustained effects. The primary adverse events associated to DEX-i injection include manageable complications such as medically controlled elevation of intraocular pressure and the development or progression of cataracts. Optimal treatment selection for individual patients with ME secondary to RVO is extremely important for achieving favorable visual and anatomical outcomes. In this pursuit, the identification of biomarkers capable of accurately predicting disease prognosis, along with the adoption of a patient-centered approach guided by their clinical characteristics, emerges as crucial strategies.